1990
DOI: 10.1093/schbul/16.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Schizophrenia on MRI Brain Scans

Abstract: There are many reports of clinical and biological gender differences in schizophrenia. Gender differences in structural brain abnormalities in schizophrenia have been reported on both computed tomographic (CT) and magnetic resonance imaging (MRI) scans. We present here a new MRI study of cerebral structures in schizophrenia. On the basis of previous findings, we hypothesized that schizophrenic males are more likely than females to show smaller brains and larger ventricles compared to their control counterparts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 12 publications
1
40
0
Order By: Relevance
“…The cortical gray matter findings are consistent with studies of cortical gray matter deficit in mixed gender samples of subjects with schizophrenia (12,13,37) but provide the first demonstration that this deficit appears to affect severely ill men and women to a similar extent. The observation of ventricular enlargement in schizophrenic women has been more controversial (19,20,22,23,(38)(39)(40), possibly because more studies have reported on this measure of brain dysmorphology. These data indicate that ventricular enlargement is as much a feature of schizophrenia in women as it is in men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cortical gray matter findings are consistent with studies of cortical gray matter deficit in mixed gender samples of subjects with schizophrenia (12,13,37) but provide the first demonstration that this deficit appears to affect severely ill men and women to a similar extent. The observation of ventricular enlargement in schizophrenic women has been more controversial (19,20,22,23,(38)(39)(40), possibly because more studies have reported on this measure of brain dysmorphology. These data indicate that ventricular enlargement is as much a feature of schizophrenia in women as it is in men.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Andreasen et al (19)(20)(21), using both computerized tomography and magnetic resonance imaging (MRI), reported a greater frequency of structural abnormalities, such as ventricular enlargement, in men with schizophrenia than in women patients. In contrast, Gur et al (22) and Nasrallah et al (23) reported greater elevation of ventricle-to-brain ratio in schizophrenic women than men. These discrepancies may be attributable to differences between both comparison and patient samples, differences in the procedures used to correct for normal variations in head size and age, and limited power of small samples to detect small effects.…”
mentioning
confidence: 84%
“…We call particular attention to the white matter fiber tracts of the corpus callosum, because we think they strongly illustrate the power of this technique in visualizing heretofore unseen fiber tracts in vivo. Summary of MR studies seporting positive and negative findings in schizophenia (Table is updated Gur et al, 1994Gur et al, , 1998bGur et al, , 1999Jernigan et al, 1991;Nasrallah et al, 1990;Rajarethinam et al, 2000;Sanfilipo et al, 2000a;Whitworth et al, 1998] − Bilder et al, 1994;Blackwood et al, 1991;Breier et al, 1992;Buchanan et al, 1993Buchanan et al, , 1998Cannon et al, 1998;Colombo et al, 1993;Dauphinais et al, 1990Flaum et al, 1995;Goldstein et al, 1999;Harvey et al, 1993;Hazlett et al, 1999;Hirayasu et al, 1998Hirayasu et al, , 2000…”
Section: Summary Of Mri Findings and Future Directions For Researchmentioning
confidence: 99%
“…Thus, the classification results can be overestimated if the data set contains chronic schizophrenia patients as well. To avoid biased results, only males were used in the analysis, as it was shown that there are differences in structural brain abnormalities in males and females [27].…”
Section: Discussionmentioning
confidence: 99%